Adapting a large database of point of care summarized guidelines: a process description. Issue 1 (7th August 2015) - Delvaux, Nicolas; Van de Velde, Stijn; Aertgeerts, Bert; Goossens, Martine; Fauquert, Benjamin; Kunnamo, Ilka; Van Royen, Paul
Abstract: Rationale, aims and objectives: Questions posed at the point of care (POC) can be answered using POC summarized guidelines. To implement a national POC information resource, we subscribed to a large database of POC summarized guidelines to complement locally available guidelines. Our challenge was in developing a sustainable strategy for adapting almost 1000 summarized guidelines. The aim of this paper was to describe our process for adapting a database of POC summarized guidelines. Methods: An adaptation process based on the ADAPTE framework was tailored to be used by a heterogeneous group of participants. Guidelines were assessed on content and on applicability to the Belgian context. To improve efficiency, we chose to first aim our efforts towards those guidelines most important to primary care doctors. Results: Over a period of 3 years, we screened about 80% of 1000 international summarized guidelines. For those guidelines identified as most important for primary care doctors, we noted that in about half of the cases, remarks were made concerning content. On the other hand, at least two‐thirds of all screened guidelines required no changes when evaluating their local usability. Conclusions: Adapting a large body of POC summarized guidelines using a formal adaptation process is possible, even when faced with limited resources. This can be done by creating an efficient and collaborative effort and ensuring user‐friendly procedures. Our experiences show that even though in most cases guidelines can be adopted without adaptations, careful review of guidelines developed in a different context remains necessary. Streamlining international efforts in adapting international POC information resources and adopting similar adaptation processes may lessen duplication efforts and prove more cost‐effective.